A Rare Case of Lymph Node Metastasis from Early Gastric Cancer - Takaaki Yoshikawa; Yoshio Kadokawa; Masaya Ohana; Akihisa Fukuda; Hiroshi Seno (Korean Society of Gastrointestinal Endoscopy, 2019)
Gastric cancers that fulfill the Japanese criteria for curative endoscopic resection show a low risk of lymph node (LN) metastasis. Here, we report a case of LN metastasis from early gastric cancer that fulfilled the curative criteria. A 74-year-old Japanese woman was referred to our hospital for treatment of early gastric cancer identified at the site of a hyperplastic polyp that had been diagnosed 10 years prior to presentation. Contrast-enhanced computed tomography did not show any lymphadenopathy and laparoscopy-assisted distal gastrectomy was performed. Histopathological examination revealed a predominantly moderately differentiated adenocarcinoma that measured 15 mm in size and was confined to the mucosa. However, a single metastatic regional LN was observed. A few cancer cells showed positive staining for alpha-fetoprotein. It should be noted that early gastric cancer can be accompanied by LN metastasis even if it fulfills the criteria for curative endoscopic resection.